2012
DOI: 10.1111/j.1461-9563.2012.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distribution of the hemlock woolly adelgid predator Laricobius nigrinus after release in eastern hemlock forests

Abstract: Post‐release distributions of Laricobius nigrinus, a biological control predator of hemlock woolly adelgid Adelges tsugae Annand, were evaluated at eight hemlock forests in the eastern U.S.A. Vertical dispersal of F1 and F2L. nigrinus were assessed from within three crown strata (<7, 7–15 and >15 m) at four release sites. Horizontal distributions of L. nigrinus within the forest surrounding central release areas were observed in two separate studies, which included (i) release and monitor to capture parent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Because of prey overlap and similar life cycles, we predicted that the dispersal rates of L. osakensis and L. nigrinus would to be similar. A previous study found that L. nigrinus dispersed at a rate of 30.6-39.2 m/year [34]. However, we were unable to obtain sufficient data on the dispersal of L. osakensis to make a comparison.…”
Section: Discussionmentioning
confidence: 77%
“…Because of prey overlap and similar life cycles, we predicted that the dispersal rates of L. osakensis and L. nigrinus would to be similar. A previous study found that L. nigrinus dispersed at a rate of 30.6-39.2 m/year [34]. However, we were unable to obtain sufficient data on the dispersal of L. osakensis to make a comparison.…”
Section: Discussionmentioning
confidence: 77%
“…has been shown to migrate vertically within trees after initial release on lower-canopy branches. Davis et al (2012) reported that L. nigrinus beetles dispersed to the upper crown (> 15 m) for oviposition, and a large proportion of subsequent larvae were collected within these crown strata at some sites. Selection of treatment branches in the present study was limited to lower crown strata (< 2 m) due to the challenges involved with the application of predator exclusion cages to branches in the upper crown.…”
Section: Discussionmentioning
confidence: 99%
“…The first operational releases of the coastal strain of L. nigrinus began in 2003 and since then, over 400,000 beetles have been released from field and laboratory sources (Virginia Tech, 2019). The ability of L. nigrinus to successfully establish and disperse from select release sites is well documented (Davis et al, 2012;Foley et al, 2019;Mausel et al, 2010), but efforts to characterize the impact of L. nigrinus on HWA populations have been few and limited in spatial scope (Mausel et al, 2008;Mayfield et al, 2015). To help inform future management decisions regarding HWA biological control, this study evaluated the impact of L. nigrinus on the HWA sistens generation and their ovisacs at several sites in the eastern U.S. where the predator has been established for multiple years.…”
Section: Introductionmentioning
confidence: 99%
“…Laricobius nigrinus or S. tsugae are established at 19 of the 35 sites used for the progrediens recovery study, but the density in the early stages of their establishment may be low. The impact of these species whose larvae feed on the progrediens stage has been difficult to document [60]. Most HWA infestations will likely have one or both of these predators present in the future, so having them at these sites during this study will incorporate their effect in future infestations.…”
Section: Progrediens Recoverymentioning
confidence: 99%